Electrochemical sensing mechanism of ammonium ions over an Ag/TiO2 composite electrode modified by hematite. Issue 18 (13th February 2023) - Zhang, Shilin; Hu, Jinqing; Li, Sam Fong Yau; Lu, Hongxiu; Wang, Gang; Lu, Chang; Sarwar, Muhammad Tariq; Tang, Aidong; Yang, Huaming
Abstract : The rapid, accurate and highly sensitive detection of NH4 + under non-alkaline conditions is achieved by electrooxidizing NH4 + to hydrazine via H2 O2 derived from the oxygen reduction reaction over a self-supporting Ag/Fe2 O3 /TiO2 sensor. Abstract : Here, we demonstrate a new electrochemical sensing mechanism of ammonium ions (NH4 + ) involving a two-electron oxygen reduction reaction (ORR) and a hydrazine reaction. The NH4 + are electrooxidized to hydrazine by H2 O2 derived from the ORR over a self-supporting Ag/TiO2 nanotube array composite electrode modified by hematite (Ag/Fe2 O3 /TNTs). The Ag/Fe2 O3 /TNT sensor exhibits a high sensitivity of 1876 µA mM −1 cm −2 with a detection limit of 0.18 µM under non-alkaline conditions, a short response time of 3 s, good reproducibility, and fine selectivity among various interferents, and is also successfully used in real water bodies to display high accuracy. Furthermore, this new mechanism has a certain universality in a range of Ag (main catalyst)/transition metal oxide (cocatalyst)/TNT sensing systems. This work offers a new design basis for the urgently needed electrochemical ammonia nitrogen sensors.